The Effects of an ICT-Based Reading Intervention on Students' Achievement in Grade Two. Issue 5 (3rd July 2016) - Schneider, Deborah; Chambers, Alex; Mather, Nancy; Bauschatz, Retina; Bauer, Meredyth; Doan, Lesli
Abstract : A controlled quasi-experimental design was used to evaluate the effects of the use of MindPlay Virtual Reading Coach on participants' reading and spelling achievement. After attrition, participants included 170 students enrolled in eight second-grade classrooms (four classrooms in each school) in two public elementary schools in the southwestern United States. MANCOVA analyses revealed a significant main effect (λ =.668, F [5, 161] = 16.014, p < 0.001, multivariate η 2 = 0.332) of the intervention favoring treatment group participants, a result that was confirmed across three of the study's five dependent variables.